Precise calibration of equilibrium oxygen isotope fractionations between dissolved phosphate and water from 3 to 37 °C. (1st February 2015) - Chang, Sae Jung; Blake, Ruth E.
Abstract: The stable oxygen isotope composition of ortho phosphate (δ 18 OPO4 ) is a widely used (paleo)temperature indicator and more recently, a useful tracer of phosphorus-cycling. In natural aqueous systems (e.g., oceans, rivers, soil/ground water) the largest reactive phosphorus pool is dissolved inorganic phosphate. Here, we present a new experimentally-determined equation for thermodynamic equilibrium O-isotope fractionations between dissolved phosphate and water, catalyzed by the enzyme inorganic pyrophosphatase (PPase) between 3 and 37 °C; 1000 ln α ( PO 4 - H 2 O ) = 14.43 ( ± 0.39 ) 1000 / T ( K ) - 26.54 ( ± 1.33 ) r 2 = 0.99 The new equation is slightly offset by +0.5 to +0.7‰ from recent empirically-determined fractionations based on biogenic apatite, with both based on modern cf-irms TC/EA analysis of Ag3 PO4 . Dissolved phosphate–water fractionations are offset by +0.9 to +2.3‰ from the earlier empirical relation for biogenic phosphate–water fractionation determined using fluorination of BiPO4 . The equation presented here is thus, specific to equilibrium fractions between dissolved phosphate and water and appropriate for use in recent/future oxygen isotope studies of dissolved phosphate using similar cf-irms TC/EA analytical methods.